IMPLEMENTASI MANAJEMEN KELAS DI MTs JABAL NURROHMAN KASREMAN KABUPATEN NGAWI JAWA TIMUR - Nurhadi Nurhadi; Maria Sanprayogi Ningsih (AL-ASASIYYA: Journal Of Basic Education, 2017)
Education has certain achievement standards such as school supervision. An educational institution is required to meet the requirements of school administration. For that, school accreditation activities are conducted to improve the quality of education, especially at the institution. Some components that must be completed to conduct school accreditation activities are the instruments related to school activities such as curriculum, educator, learning process, facilities and infrastructure and financing. In the standard of facilities and infrastructure, the existence of the class becomes the core assessment as it relates to teaching and learning activities. After class physical fulfillment, good and conducive class management becomes the determinant of the effectiveness of learning activities. Therefore, good classroom management is necessary.